2021
DOI: 10.1111/pirs.12595
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to rural entrepreneurship

Abstract: This study offers a novel approach to understand the mechanisms of rural entrepreneurship by applying five alternative machine learning techniques on data obtained from the Life in Transition Survey III. Results highlight how capital constraints, age, factors related to trust and over-trust, awareness of current trends, the use of various media tools, a competitive character, institutional factors, and education are associated with the success and failure of potential entrepreneurs in rural areas who attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
0
10
0
1
Order By: Relevance
“…On the other hand, while we observed that initial health status is also important in the private sector, there have been distinct attributes related to age, industry, and mobility/stringency effects – particularly in the retail and recreation category – that had even stronger effects on employment outcomes. Such stringency policies may lead to long‐term impacts for the individuals in the self‐employed group as trust in governments and institutions are crucial factors that support entrepreneurial behavior (Celbiş, 2021b ). Education alongside health are found to be important determinants for persons born before 1955.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 99%
“…On the other hand, while we observed that initial health status is also important in the private sector, there have been distinct attributes related to age, industry, and mobility/stringency effects – particularly in the retail and recreation category – that had even stronger effects on employment outcomes. Such stringency policies may lead to long‐term impacts for the individuals in the self‐employed group as trust in governments and institutions are crucial factors that support entrepreneurial behavior (Celbiş, 2021b ). Education alongside health are found to be important determinants for persons born before 1955.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 99%
“…Business startups in rural areas depend on various factors, including the economic context (e.g., agglomeration forces and banking environment), demographics (e.g., age composition, education, and gender), local environment (e.g., natural amenities, such as green spaces, water areas, and topographic conditions), and public policies (e.g., labor regulation; Celbiş, 2021; Markeson & Deller, 2012; Naldi et al, 2021).…”
Section: Contingent Effect Of Broadband On Business Startupsmentioning
confidence: 99%
“…Alongside local economic conditions, the literature has concentrated on the role of demographics, particularly education and age composition, as major determinants of new firm formation in rural areas (Artz et al, 2021; Celbiş, 2021).…”
Section: Contingent Effect Of Broadband On Business Startupsmentioning
confidence: 99%
“…Past research has shown that entrepreneurship and human capital are key determinants of innovative activity and crucial factors of development in lagging areas [57][58][59][60]. Together with human capital, measured by the level of education (Degree), we include variables that measure the importance of entrepreneurs (Self) and of private industry (Private) within the model.…”
Section: Theoretical Backgroundmentioning
confidence: 99%